Screening, prevalence, treatment and control of kidney disease in patients with type 1 and type 2 diabetes in low-to-middle-income countries (2005–2017): the International Diabetes Management Practices Study (IDMPS) - Mbanya, Jean Claude (2021)
Diabetes is the leading cause of kidney disease worldwide. There is limited information on screening, treatment and control of kidney disease in patients with diabetes in low-to-middle-income countries (LMICs).